Efeitos do reforçamento positivo sobreposto à punição negativa na aquisição e manutenção de autorrelatos correspondentes de crianças - Tarifa, Ana Luisa Galharde (Universidade Federal de São Carlos, 2025)
The present study evaluated the effects of positive reinforcement for corresponding reports combined with negative punishment for non-corresponding reports on the acquisition and maintenance of corresponding self-reports in children. “Doing” consisted of naming a numeral or the result of a mathematical operation, while “saying” involved reporting whether the response was correct or incorrect following computer feedback. Five children participated and were exposed to four experimental conditions: (1) baseline, in which report accuracy was assessed in a situation with no differential consequences for corresponding or non-corresponding reports; (2) correspondence training, in which corresponding reports were followed by point delivery (positive reinforcement), while non-corresponding reports resulted in point removal (negative punishment); and (3) maintenance, in which correspondence was assessed in a situation with no differential consequences. For three participants who exhibited high correspondence levels in the baseline, a contingent reinforcement condition for reports of correct responses was introduced before the correspondence training condition. Positive reinforcement for corresponding reports superimposed with punishment for non-corresponding reports produced high correspondence levels (90–100%) in a few sessions (3–6) for all participants, which were maintained after 15 and 30 days for three of the five participants.
Effects of positive reinforcement combined with negative punishment on the acquisition and maintenance of corresponding self-reports in children
Keywords: Correspondência fazer-dizer; Manutenção; Punição negativa; Treino de correspondência; Relato verbal; CIENCIAS HUMANAS::PSICOLOGIA